(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
A thickened bronchial wall is the morphological substratum of most diseases of the airway. Theoretical and clinical models of bronchial morphometry have so far focused on bronchial lumen diameter, and bronchial length and angles, mainly assessed from bronchial casts. However, these models do not provide information on bronchial wall thickness. This article reports in vivo values of cross-sectional wall area, lumen area, wall thickness and lumen diameter in ten healthy subjects as assessed by multi-detector computed tomography.Measured lumen diameters and homothety ratios were compared with theoretical values obtained from previously published studies, and no difference was found when considering dichotomic division of the bronchial tree. Multi-detector computed tomography measurements of bronchial morphometric parameters may help to improve our knowledge of bronchial anatomy in vivo, our understanding of the pathophysiology of bronchial diseases and the evaluation of pharmacological effects on the bronchial wall.